ANALYSIS OF RISK FACTORS AFFECTING LUMBAL FACET JOINT OSTEOARTHRITIS IN MRI SCAN - Aulia Anastasia; Hermina Sukmaningtyas; Agus Priambodo; Erna Setiawati (Faculty of Medicine, Universitas Diponegoro, Semarang, Indonesia, 2022)
Background: Osteoarthritis is a long-term, chronic disease that is usually marked by cartilage degeneration in the joints, which in turn induces bone friction. One of the subtype of this disease is facet joint osteoarthritis or in short, FJOA. In Indonesia, FJOA has not been commonly documented. The most common method for FJOA inspection is X-Ray modality. The usage of other radiology imaging, such as CT-Scan or MRI, are also used to evaluate erosion, osteophyte creation, subchondral sclerosis, and joint constriction. Nevertheless, the most ideal FJOA inspection method is still an ongoing debate due to strengths and weaknesses of each methods. CT scans are more widely used than MRIs and are typically less expensive. MRIs, however, are thought to be superior in regards to the detail of the image. Objective: To understand the effect of age, sex, and spinal level towards FJOA on MRI scanning. Method: This research used cross-sectional approach. Sample taken in this research were all radiology results from patients that fulfills inclusion criteria and had gone through MRI inspection in Jatinegara Premier Hospital. Age, sex, disk degeneration degree, and spinal level are the main focus for this study since those are the most common risk factor for FJOA. Results: 46.8% of FJOA were found in male patients while the other 53.2% were found in females. L4-5 and Grade 1 FJOA had the highest incidence found, with the amount of 29% and 48.4% respectively. There was no correlation between sex and FJOA degree based on Asymp. Sig of 0.255. There was also no correlation between age and FJOA degree based on Asymp. Sig of 0.702. However, there was a correlation between spinal level and disk degeneration degree with FJOA degree due to Asymp. Sig <0.05. Conclusion: There was no significant relationship between age and sex to lumbar facet joint osteoarthritis and there was a significant relationship between spinal level and disk degeneration degree with lumbar facet joint osteoarthritis.